Role of Host and Pathogen-Derived MicroRNAs in Immune Regulation During Infectious and Inflammatory Diseases - Chandan, Kumari; Gupta, Meenakshi; Sarwat, Maryam (Frontiers in Immunology, 2020)
MicroRNAs (miRNAs, miRs) are short, endogenously initiated, non-coding RNAs that bind to target mRNAs, leading to the degradation or translational suppression of respective mRNAs. They have been reported as key players in physiological processes like differentiation, cellular proliferation, development, and apoptosis. They have gained importance as gene expression regulators in the immune system. They control antibody production and release various inflammatory mediators. Abnormal expression and functioning of miRNA in the immune system is linked to various diseases like inflammatory disorders, allergic diseases, cancers etc. As compared to the average human genome, miRNA targets the genes of immune system quite differently. miRNA appeared to regulate the responses related to both acquired and innate immunity of the humans. Several miRNAs importantly regulate the transcription and even, dysregulation of inflammation-related mediators. Many miRNAs are either upregulated or downregulated in various inflammatory and infectious diseases. Hence, modifying or targeting the expression of miRNAs might serve as a novel strategy for the diagnosis, prevention, and treatment of various inflammatory and infectious conditions.